MODEL TEORETIKAL DASAR ALIANSI STRATEJIK SEBAGAI STRATEGIC KNOWLEDGE MENUJU KEUNGGULAN BERSAING BERKELANJUTAN - Widodo . (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2011)
Strategic alliance is a business strategy undertaken by two or more parties within a specified period to achieve mutual benefits with the principle of mutual need and encouraging. It starts by getting to know prospective partners, knowing the position of the advantages and disadvantages of business, start building a strategy, implement, monitor, and evaluate until the target is reached. Organizational learning processes strategically is pointing to the insight (an effort to find new things) and future outlook. It was de with a tie between knowledge creation with continuous innovation and also impute constant innovation with the competitive advantage.Therefore, strategic knowledge is knowledge that is created as a consequence of the learning process in cooperation (alliance).Key word : Aliancy strategic, strategic knowledge, sustainable competitive advantage